The COSMIC Cancer Gene Census: describing genetic dysfunction across all human cancers. Issue 11 (November 2018) - Sondka, Zbyslaw; Bamford, Sally; Cole, Charlotte; Ward, Sari; Dunham, Ian; Forbes, Simon
Abstract The Catalogue of Somatic Mutations in Cancer (COSMIC) Cancer Gene Census (CGC) is an expert-curated description of the genes driving human cancer that is used as a standard in cancer genetics across basic research, medical reporting and pharmaceutical development. After a major expansion and complete re-evaluation, the 2018 CGC describes in detail the effect of 719 cancer-driving genes. The recent expansion includes functional and mechanistic descriptions of how each gene contributes to disease generation in terms of the key cancer hallmarks and the impact of mutations on gene and protein function. These functional characteristics depict the extraordinary complexity of cancer biology and suggest multiple cancer-related functions for many genes, which are often highly tissue-dependent or tumour stage-dependent. The 2018 CGC encompasses a second tier, describing an expanding list of genes (currently 145) from more recent cancer studies that show supportive but less detailed indications of a role in cancer. This Review discusses the 2018 Catalogue of Somatic Mutations in Cancer (COSMIC) Cancer Gene Census (CGC), an expert-curated description of human cancer genes, which has recently been expanded to include functional descriptions of how each gene contributes to cancer.